ANALISA FAKTOR - FAKTOR YANG MEMPENGARUHI KUALITAS AUDIT YANG DILAKUKAN OLEH BADAN PEMERIKSA KEUANGAN REPUBLIK INDONESIA (Studi Kasus pada BPK RI Perwakilan Provinsi Kepulauan Bangka Belitung) - Arista Rizky Indriyanto; Nasi kin (Jurnal Ilmiah Mahasiswa FEB, 2014)
The  purpose  of  this  research  is  to  examines  the  influence  of  auditor’s educational  background,  auditor’s  experience,  auditor’s  training  hours,  audit structure,  role  conflict,  and  role ambiguity  on  BPK  RI  Perwakilan  Provinsi Kepulauan Bangka Belitung’s  audit  quality. The  number  of  respondents  in  this research are 34 auditors. This research is using a cencus method as the method of determining the sample, because the number  of  the  population  is  under  100 respondent.  Data  processing  methods  that  used  in  this  research  is  multiple regression analysis.The result of this research shows auditor’s educational background, auditor’sexperience,  auditor’s  training  hours,  audit  structure,  role  conflict,  and  roleambiguity simultaneously and significantly influence BPK RI Perwakilan ProvinsiKepulauan Bangka Belitung’s audit quality. Partially, only role conflict and roleambiguity  significantly  influence  the  audit  quality.  Auditor’s  educationalbackground,  auditor’s  experience,  auditor’s  training  hours,  and  audit  structureunsignificantly influence the audit quality.Keywords : auditor’s  educational  background,  auditor’s  experience, auditor’straining hours, audit structure, role conflict, role ambiguity, audit quality, bpk ri.